2021
DOI: 10.1007/s11695-021-05728-9
|View full text |Cite
|
Sign up to set email alerts
|

Revisional One Anastomosis Gastric Bypass with a 150-cm Biliopancreatic Limb After Failure of Adjustable Gastric Banding: Mid-Term Outcomes and Comparison Between One- and Two-Stage Approaches

Abstract: Purpose Laparoscopic adjustable gastric banding (LAGB) was a common procedure worldwide but associated with a high rate of long-term failure. This study aims to evaluate the safety and effectiveness of conversion to one anastomosis gastric bypass (OAGB) after failed LAGB. Materials and Methods We undertook a retrospective analysis of a prospectively maintained database in a tertiary referral center for bariatric surgery. All cases of revisional OAGB with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
2
2
0
Order By: Relevance
“…As for re-OAGB, we found an EWL of 86.7% 2 years after revisional surgery. This percentage was comparable to the EWL of 88.2% and 84.1% at 2-years follow-up in two studies by Petrucciani et al 44 and Debs et al, 45 and to the EWL of 79% in a study by Gerges et al 46 evaluating re-OAGB after failure of restrictive procedure. The remarkable difference we found in weight loss outcome (EWL: 86.7% vs 54%) between re-OAGB and re-LSG 2 years after revisional surgery underlines the inferior efficacy of re-adopting a revisional restrictive surgery after an initial failure of primary restrictive surgery, which comes in accordance with two other studies 29,47 that showed a superiority of gastric bypass conversion compared with re-LSG after failure of restrictive surgery.…”
Section: Discussionsupporting
confidence: 75%
“…As for re-OAGB, we found an EWL of 86.7% 2 years after revisional surgery. This percentage was comparable to the EWL of 88.2% and 84.1% at 2-years follow-up in two studies by Petrucciani et al 44 and Debs et al, 45 and to the EWL of 79% in a study by Gerges et al 46 evaluating re-OAGB after failure of restrictive procedure. The remarkable difference we found in weight loss outcome (EWL: 86.7% vs 54%) between re-OAGB and re-LSG 2 years after revisional surgery underlines the inferior efficacy of re-adopting a revisional restrictive surgery after an initial failure of primary restrictive surgery, which comes in accordance with two other studies 29,47 that showed a superiority of gastric bypass conversion compared with re-LSG after failure of restrictive surgery.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies have demonstrated increased prevalence of GERD in bariatric surgery candidates, which was in a range from 40.8% to 62.4% [6][7][8]. Similarly, 41.1% of bariatric surgery patients presenting in our center had GERD preoperatively.…”
Section: Discussionsupporting
confidence: 52%
“…However, the possible mechanisms of GERD persistence or the new onset after RYGB are poorly understood. Petrucciani N., et al [8] have found that preoperative GERD (OR=2.65, p<0.0001), glycemic imbalances defined as post-prandial symptoms, which has impact on quality of life and occurs at least more than 2 times per month (OR=0.32, p=0.006), anastomotic ulcer (OR=0.35, p<0.0001) and %TWL at 10 years ≥25 (OR=0.524, p= 0.021) were significant risk factors related to GERD 10 years after RYGB [8]. We were unable to confirm the finding that preoperative GERD has influence on the GERD 12 years after surgery because more patients in our study had de novo GERD as compared to those who had persistent GERD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation